Review of the genus Myrmozercon Berlese (Acari: Laelapidae), with description of two new species from Iran - Joharchi, Omid; Moradi, Maryam (Zootaxa, 2013)
This paper reports on three species of mites of the genus Myrmozercon Berlese, 1902 associated with ants in Iran – Myrmozercon crinitus Joharchi sp. nov. from Pheidole pallidula (Nylander), Myrmozercon michaeli Joharchi sp. nov. from Messor sp. and Myrmozercon tauricus Trach & Khaustov from Crematogaster schmidti (Mayr) in the bark of grape vines. Myrmozercon is re-deﬁned, the distribution, and the host-speciﬁcity and host range of its constituent species are discussed. A key to species of Myrmozercon occurring in the Palaearctic Region is presented.